2007
DOI: 10.1128/jb.01845-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Gene Cluster from Pseudomonas syringae pv. phaseolicola NPS3121 Involved in Synthesis of Phaseolotoxin

Abstract: Pseudomonas syringae pv. phaseolicola is the causal agent of halo blight disease of beans (Phaseolus vulgaris L.), which is characterized by water-soaked lesions surrounded by a chlorotic halo resulting from the action of a non-host-specific toxin known as phaseolotoxin. This phytotoxin inhibits the enzyme ornithine carbamoyltransferase involved in arginine biosynthesis. Different evidence suggested that genes involved in phaseolotoxin production were clustered. Two genes had been previously identified in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(110 citation statements)
references
References 43 publications
5
80
0
Order By: Relevance
“…In cells grown at 28-30°C, phaseolotoxin is not produced and OCT remains fully sensitive [216]. Two genes encoding OCT activity, argF and argK, are present in the producer [170] and one of them (argK, encoding ROCT) is located within the phaseolotoxin-biosynthetic cluster [1]. According to one model [126], temperature downshift is sensed in P. syringae pv.…”
Section: Target Ornithine Carbamoyltransferase: Phaseolotoxinmentioning
confidence: 99%
“…In cells grown at 28-30°C, phaseolotoxin is not produced and OCT remains fully sensitive [216]. Two genes encoding OCT activity, argF and argK, are present in the producer [170] and one of them (argK, encoding ROCT) is located within the phaseolotoxin-biosynthetic cluster [1]. According to one model [126], temperature downshift is sensed in P. syringae pv.…”
Section: Target Ornithine Carbamoyltransferase: Phaseolotoxinmentioning
confidence: 99%
“…phaseolicola, appears to increase virulence, and is responsible for the development of a yellow halo surrounding the watersoaked lesions characteristic of the disease (Bender et al, 1999;Patil et al, 1974). Resistance of the pathogen to its own toxin is due to production of a phaseolotoxinresistant OCTase, encoded by the argK gene, which is located, together with the biosynthetic genes, in a chromosomal region known as the argK-tox cluster (Aguilera et al, 2007;Genka et al, 2006;Mosqueda et al, 1990). Most isolates of P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are more reports on the biosynthesis of peptidic secondary metabolites involving nonribosomal peptide synthetase than reports describing Lals (26). Rhizocticin and phaseolotoxin are di-or tripeptide antibiotic and tripeptide phytotoxins, respectively, that contain an unusual amino acid, and two ATP-grasp enzymes were identified in each biosynthetic gene cluster (27,28). In rhizocticin biosynthesis, our results revealed that two Lals (RizA and RizB) combined three amino acids, yielding tripeptides similar to rhizocticin (19,20).…”
mentioning
confidence: 69%